Urban physical characteristics for sense of security - Sedaghatfard, Mohammad; Soltani, Ali (TeMA - Journal of Land Use, Mobility and Environment, 2025)
This research delves into the symbiotic nexus between the morphology of the urban fabric and the phenomenology of security. Situated in Shiraz, Iran, this inquiry interrogates the determinative role of four morphological attributes; green spaces, land use, illumination, and network connectivity, juxtaposed against socio-economic traits. Through a dialectical comparison of two ontologically distinct urban enclaves, we employ structural equation modelling to forge and empirically ground the Physical Attributes Affecting Sense of Security Model (PAASSM). The analysis reveals that the city’s corporeal fabric, principally its land use and green commons, are primary architects of the citizen’s sense of sanctuary, with socio-economic variables exerting a subordinate yet non-trivial influence. The superior security manifest in the city’s modern, planned district stands as a testament to the virtues of deliberate spatial ordering. Ultimately, this study bequeaths a novel epistemological framework, articulating a new mandate for urban praxis: to recognize the deliberate sculpting of the built form as a primary instrument for cultivating a safer, more resilient, and socially cohesive polis.